The Impact of Foreign Direct Investment (FDI) on Economic Growth in Deli Serdang Regency 2015-2024 - Evida Rahimah; Zulaili; Radiah; Supriono; Ilfi Rahmi Putri (Yayasan pendidikan dzurriyatul Quran, 2026)
This study is entitled